PENGARUH WORD OF MOUTH DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI ENVIO STORE RUNGKUT SURABAYA - Fina Idamatussilmi Idamatussilmi; Agung Pujianto; Ayun Maduwinarti (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
Tlhe purpollse of this research is to find out and anallyze the effect of word of mouth and prilce on product purchasing decisions at Envio Store Rungkut Surabaya. This research method uses quantitative reselarch methods with non-probability sampling telchniques in the forml of purposive sampling. The poplulation in this study were people who had bought prlodul cts at the Envio Store Rungkut Surabaya, with a totl al sample of 96 respondents. The method of data analysl is in this study was to use multiple regression analysis tests, validity tests, multicollinearity tests, heteroscedasticity tests and hypothesis testing consisting of t tests, determination tests, r tests wlith the help of the IBM SPSS version 25 for window prlogram. The results and conclusions of this study indicate that word of mouth and price have a positive and signlificant effect both palrtially and simultal neously on prodluct purchasing declisions at Envio Store Rungkut Surabaya.